Knockdown of nrf2 Exacerbates TNF-α-Induced Proliferation and Invasion of Rheumatoid Arthritis Fibroblast-Like Synoviocytes through Activating JNK Pathway - Yu Du; Qian Wang; Na Tian; Meng Lu; Xian-Long Zhang; Sheng-Ming Dai (Journal of Immunology Research)
Fibroblast-like synoviocytes (FLS) in the synovial tissue of rheumatoid arthritis (RA) exhibit over-proliferative and aggressive phenotypes, which participate in the pathophysiology of RA. In RA, little is known about the nonantioxidant effect of nuclear factor erythroid 2-related factor 2 (nrf2), the master regulator of redox homeostasis. In this study, we aimed to explore the expression and upstream regulatory factors of nrf2 and revealed its functions in modulating the proliferation and invasion in RA-FLS. FLS were isolated from RA and osteoarthritis patients. Expression of nrf2 in the synovial tissues and FLS was analyzed by immunohistochemistry, real-time PCR, Western blotting, and immunofluorescence staining. Cell proliferation was examined by Cell Counting Kit-8. Cell invasion was tested by transwell assay. Phosphorylation of JNK was determined by Western blotting. The results showed that nrf2 expression in the RA synovial tissues was upregulated. TNF-α promoted expression and nuclear translocation of nrf2 in RA-FLS and increased the intracellular reactive oxygen species (ROS) level. Nrf2 nuclear translocation was blocked by ROS inhibitor N-acetylcysteine. Both knockdown of nrf2 by siRNA and inhibition of nrf2 by ML385 significantly promoted the TNF-α-induced proliferation and invasion of RA-FLS. Activation of nrf2 by sulforaphane (SFN) profoundly inhibited the TNF-α-induced proliferation and invasion of RA-FLS. Knockdown of nrf2 also enhanced the TNF-α-induced matrix metalloproteinases (MMPs) expression and phosphorylation of JNK in RA-FLS. Proliferation and invasion of RA-FLS incubated with TNF-α and nrf2 siRNA were inhibited by pretreatment with JNK inhibitor SP600125. In conclusion, nrf2 is overexpressed in synovial tissues of RA patients, which may be promoted by TNF-α and ROS levels. Activation of nrf2 may suppress TNF-α-induced proliferation, invasion, and MMPs expression in RA-FLS by inhibiting JNK activation, indicating that nrf2 plays a protective role in relieving the severity of synovitis in RA. Our results might provide novel insights into the treatment of RA.